(untitled) (Journal of Basic and Applied Research in Biomedicine, 2016)
Alley cropping system can play a significant contribution of the multiple components of yield especially in hot regions. This study was carried out at the Tropical Farm of Kom-Ombo, Aswan, Egypt during 2012/2013 and 2013/2014 seasons to investigate the value of growing pea plants under alley cropping with two tree species; the Egyptian river hemp (Sesbania sesban) and white lead tree (Leucaena leucocephala) and three levels of nitrogen fertilization. Sole pea plants which received the recommended N dose (RD) were considered as control. The results indicated that yield and yield components of pea plants were significantly affected with alley cropping. Moreover, the highest values of seed fresh weight were noticed in pea plants allied with Leucaena+1/2 RD. On the other hand, pea allied with Sesbania+1/2 RD of N gave the best results for seeds dry yield, number of seeds/pod, seeds weight/pod, weight of 100 seeds, fresh weight of pod and pod length and diameter. For seed chemical compositions and quality, it was noticed that the lowest NO3 and NO2 contents were due to growing pea plants with Leucaena or Sesbania trees without any N fertilization. The highest seeds total carbohydrate % was for plants allied with Sesbania. However, pea plants allied with Sesbania+1/2 RD gave the highest seeds protein %. The land equivalent ratio of pea with Sesbania or Leucaena showed that this system had better seed yield performance when compared to sole cropping. Therefore, alley cropping with legume trees can reduce fertilizer requirement for vegetable production. Pea, a cool season crop, can be grown under the hedgerow of trees in hot region like Aswan, Egypt and give more production than sole system.